Transcranial Magnetic Stimulation to Address Mild Cognitive Impairment in the Elderly: A Randomized Controlled Study - Hellen Livia Drumond Marra; Martin Luiz Myczkowski; Cláudia Maia Memória; Débora Arnaut; Philip Leite Ribeiro; Carlos Gustavo Sardinha Mansur; Rodrigo Lancelote Alberto; Bianca Boura Bellini; Adriano Alves Fernandes da Silva; Gabriel Tortella; Daniel Ciampi de Andrade; Manoel Jacobsen Teixeira; et al. (Behavioural Neurology)
Transcranial magnetic stimulation (TMS) is a noninvasive brain stimulation technique with potential to improve memory. Mild cognitive impairment (MCI), which still lacks a specific therapy, is a clinical syndrome associated with increased risk of dementia. This study aims to assess the effects of high-frequency repetitive TMS (HF rTMS) on everyday memory of the elderly with MCI. We conducted a double-blinded randomized sham-controlled trial using rTMS over the left dorsolateral prefrontal cortex (DLPFC). Thirty-four elderly outpatients meeting Petersen’s MCI criteria were randomly assigned to receive 10 sessions of either active TMS or sham, 10 Hz rTMS at 110% of motor threshold, 2,000 pulses per session. Neuropsychological assessment at baseline, after the last session (10th) and at one-month follow-up, was applied. ANOVA on the primary efficacy measure, the Rivermead Behavioural Memory Test, revealed a significant group-by-time interaction p=0.05, favoring the active group. The improvement was kept after one month. Other neuropsychological tests were heterogeneous. rTMS at 10 Hz enhanced everyday memory in elderly with MCI after 10 sessions. These findings suggest that rTMS might be effective as a therapy for MCI and probably a tool to delay deterioration.